LEXICAL VARIATION IN THE MOSAIC OF URDU PROSE - Syed Alamdar Nabi, Safia Asif, Lubna Yasir, Muhammad Imran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research investigated diachronic variation in Urdu writings in prose. In the present research, representative writers of prose from different ages were selected for analysis of their writings for language variation. These writers are Mir Aman, Asad ul Allah Ghalib, Deputy Nazeer Ahmed, Saadat Hasan Munto, Qurat ul Ain Haider, and Ahmad Nadeem Qasmi. The investigation indicated that Urdu prose writings had undergone a complex evolution. The analysis reveals that the old version of Urdu writing processed through complex fruition. The complex, wordy and loquacious fabric of Urdu language changes into a simple and communicative lingua franca. However, this simplicity does not turn new language into taciturn usage of language. Different phases of evolution were found as the key variational milestones in Urdu prose. These variational segments and proportional combination of the words from different languages in Urdu prose are found as significant findings in this research.